A Role for Drosophila Amyloid Precursor Protein in Retrograde Trafficking of L1-Type Cell Adhesion Molecule Neuroglian - Penserga, Tyrone; Kudumala, Sirisha Rani; Poulos, Richelle; Godenschwege, Tanja Angela (Frontiers in Cellular Neuroscience, 2019)
The role of the Amyloid Precursor Protein (APP) in the pathology of Alzheimer's disease (AD) has been well studied. However, the normal function of APP in the nervous system is poorly understood. Here, we characterized the role of the Drosophila homologue (APPL) in the adult giant fiber (GF) neurons. We find that endogenous APPL is transported from the synapse to the soma in the adult. Live-imaging revealed that retrograde moving APPL vesicles co-traffic with L1-type cell adhesion molecule Neuroglian (Nrg). In APPL null mutants, stationary Nrg vesicles were increased along the axon, and the number of Nrg vesicles moving in retrograde but not anterograde direction was reduced. In contrast, trafficking of endo-lysosomal vesicles, which did not co-localize with APPL in GF axons, was not affected. This suggests that APPL loss of function does not generally disrupt axonal transport but that APPL has a selective role in the effectiveness of retrograde transport of proteins it co-traffics with. While the GF terminals of APPL loss of function animals exhibited pruning defects, APPL gain of function had no disruptive effect on GF morphology and function, or on retrograde axonal transport of Nrg. However, cell-autonomous developmental expression of a secretion-deficient form of APPL (APPL-SD), lacking the α-, β- and, -secretase cleavage sites, resulted in progressive retraction of the GF terminals. Conditional expression of APPL-SD in mature GFs caused accumulation of Nrg in normal sized synaptic terminals, which was associated with severely reduced retrograde flux of Nrg labeled vesicles in the axons. Albeit β-secretase null mutants developed GF terminals they also exhibited Nrg accumulations. This suggests that cleavage defective APPL has a toxic effect on retrograde trafficking and that β-secretase cleavage has a function in Nrg sorting in endosomal compartments at the synapse. In summary, our results suggest a role for APPL and its proteolytic cleavage sites in retrograde trafficking, thus our findings are of relevance to the understanding of the endogenous role of APP as well as to the development of therapeutic treatments of Alzheimer’s disease.